TINJAUAN HUKUM PIDANA ISLAM TERHADAP ANAK SEBAGAI PELAKU TINDAK PIDANA PENGEROYOKAN - Adriani, Erin Novi; Azizah, Noor (Legal Standing : Jurnal Ilmu Hukum, 2024)
This research delves into the role of children in the continuity of the nation and state, particularly in the context of criminal acts of child assault. The research focuses on understanding the considerations of judges in imposing sanctions and the application of these sanctions from the perspective of Islamic criminal law. Utilizing a qualitative approach and referring to the normative framework, data were collected through literature research, analysis of legal publications, and examination of relevant court decisions. Comprehensive analysis was conducted by evaluating judges and the imposition of sentences in the context of positive Indonesian criminal law. This study seeks to make a significant contribution to deepening the understanding of child protection in the legal realm, considering both positive legal aspects and the values of Islamic criminal law. The findings of this research are expected to provide deeper insights into the challenges and solutions that can be applied to protect children from acts of assault. The implications of these research findings can serve as a basis for formulating policy recommendations aimed at enhancing child protection from assault crimes. These recommendations may include concrete steps that can be taken by the government, legal institutions, and the community to create a safer and more supportive environment for children. As part of the effort to build a fair and just legal system, this research is expected to offer a holistic perspective on this issue, considering both the positive legal perspective and the values of Islamic law.